EFFECT OF DIFFERENT MEDIA ON GROWTH AND SPORULATION OF CERCOSPORA ARACHIDICOLA CAUSING EARLY LEAF SPOT OF GROUND NUT - V. SURENDRA; SUNIL ZACHARIA; K. RAMANA REDDY; N. P. ESWARA REDDY; P. CHOWDAPPA (The Bioscan, 2015)
The pathogen of ground nut early leaf spot, Cercospora arachidicola was inoculated on Potato sucrose agar, Oatmeal agar, Potato dextrose agar, V8-juice agar, Leaf extract agar, Carrot juice agar and Peanut hull extract agar. Out of all the media tested, the maximum growth was supported by Potato Sucrose Agar followed by Oat Meal Agar at 23±1ºC and more than 90% relative humidity. Maximum sporulation of C. arachidicola was obtained in Potato Sucrose Agar at 6 per cent sucrose followed by 5 per cent.